2012
DOI: 10.2486/indhealth.ms1315
|View full text |Cite
|
Sign up to set email alerts
|

The 60-Film Set with 8-index for Examining Physicians’ Proficiency in Reading Pneumoconiosis Chest X-rays

Abstract: abstract:The 60-film set was developed by experts (expert group) for examining 8 indices: sensitivity (X 1 ) and specificity (X 2 ) for pneumoconiosis, sensitivity(X 3 ) and specificity for (X 4 ) large opacities, sensitivity (X 5 ) and specificity (X 6 ) for pleural plaque, profusion increment consistency for small opacities (X 7 ), and shape differentiation for small opacities (X 8 ) of physicians' reading skills on pneumoconiosis X-ray according to ilO 2000 classification. The aim of this study was to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Factor analysis showed that the Factor 2 scores in the A1-Group and A2-Group were significantly higher than those in the B-Group, which were consistent with the results as shown in Table 2 in our previous literature that the sensitivity for pneumoconiosis of A2-Group, and the sensitivity for large opacities of both A1-Group and A2-Group were higher than those in the B-Group 1) . This indicated that A1-Group and A2-Group tended to identify much more parenchymal abnormalities than the B-Group.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…Factor analysis showed that the Factor 2 scores in the A1-Group and A2-Group were significantly higher than those in the B-Group, which were consistent with the results as shown in Table 2 in our previous literature that the sensitivity for pneumoconiosis of A2-Group, and the sensitivity for large opacities of both A1-Group and A2-Group were higher than those in the B-Group 1) . This indicated that A1-Group and A2-Group tended to identify much more parenchymal abnormalities than the B-Group.…”
supporting
confidence: 91%
“…In the current authors' preceding paper 1) , we have suggested that 8 indices reflect reading proficiency for pneumoconiosis in individuals and groups and be used appropriately for assessing examination results from reading 60-film sets: sensitivity for pneumoconiosis, specificity for pneumoconiosis, sensitivity for large opacities, specificity for large opacities, sensitivity for pleural plaque, specificity for pleural plaque, profusion increment consistency for small opacities, and shape differentiation for small opacities. The exam films, the correct answers, the criteria for 8 indices in 60 exam films, and the assessment algorithm were described in the Appendix in the literature 1) .…”
mentioning
confidence: 99%
See 3 more Smart Citations